(untitled) (Abhat Journal, 2024)
The research deals with studying the issue of the res judicata of arbitral awards in Libyan Law, with the aim of defining the meaning of the res judicata of arbitral awards and the extent to which arbitration awards enjoy it, and knowing the conditions for adhering to the validity of the final award. It also distinguishes between the res judicata of arbitral awards and similar concepts, in addition to knowing the scope of the res judicata of arbitral awards in terms of subject matter and persons, and enriching the Arab legal library in this field. The research problem focus on the extent to which arbitral awards are res judicata in Libyan law? Answering that, we used the analytical and comparative approaches. To reach satisfactory conclusion, this paper is divided into two sections, The first deals with the definition of the res judicata of arbitral awards, and the second discusses its scope and its relation with public order.